Incorporating climate change into conservation planning: Identifying priority areas across a species’ range - Richard G Pearson; Eleanor J Sterling; Karl Didier; Kent H Redford; Mary E Blair; Robert A Rose; Peter J Ersts; Eric W Sanderson (Frontiers of Biogeography, 2012)
Theoretical and practical approaches associated with conservation biogeography, including ecological niche modeling, have been applied to the difficult task of determining how to incorporate climate change into conservation prioritization methodologies. Most studies have focused on identifying species that are most at risk from climate change, but here we asked, which areas within a species’ range does climate change threaten most? We explored methods for incorporating climate change within a range-wide conservation planning framework, using a case study of jaguars (Panthera onca). We used ecological niche models to estimate exposure to climate change across the range of the jaguar and incorporated these estimates into habitat quality scores for re-prioritization of high-priority areas for jaguar conservation. Methods such as these are needed to guide prioritization of geographically-specific actions for conservation across a species’ range.